Drivers of treatment patterns in patients with chronic lymphocytic leukemia stopping ibrutinib or idelalisib therapies. Issue 7 (3rd July 2018) - Mato, Anthony R.; Samp, Jennifer C.; Gauthier, Geneviève; Terasawa, Emi; Brander, Danielle M.
ABSTRACT: Novel therapies including kinase inhibitors (KI) have led to high and durable response in patients with chronic lymphocytic leukemia (CLL), however, some patients stop therapy. This study evaluates reasons for treatment changes among CLL patients who stopped KI in real-world practice. Sixty-nine US oncologists/hematologists provided patient-level data abstracted from charts of CLL adult patients who initiated a KI and later (1) switched to another anti-neoplastic regimen ( Switched cohort), (2) discontinued the KI and remained untreated ( Discontinued cohort), or (3) restarted the same KI after an interruption of ≥60 days (Restarted cohort). Demographics, clinical/treatment characteristics, and reasons for stopping, restarting, and switching the KI therapy were described. In the Switched cohort, reasons for stopping included disease progression (72.5%), low/no disease activity (3.9%), adverse event [AE]/ intolerance/comorbidity (15.7%), and planned cellular therapies (7.9%). In the Discontinued cohort, approximately half (46.0%) of patients stopped KI therapy because they were terminally ill/died, or were moved to best supportive care — these patients were older, had more severe disease, and high comorbidity burden. The other half (54.0% of patients) stopped due to low/no disease activity (24.0%), AEs/toxicity (12.0%), or patient-requested drug holiday (18.0%). In the Restarted cohort, the most common reasons for stopping KIs were patient request (37.3%), AEs/intolerance (31.4%), and economic reasons (10%). Patients restarted when disease progressed (60.8%) or when they recovered from the AE (33%). Reasons for KI stop and subsequent treatment patterns were varied and multifactorial, suggesting heterogeneous disease management and a need for more evidence around supporting strategies and physician education.